2013
DOI: 10.1371/journal.pone.0058005
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Patterns Associated with Colonization of Different Clostridium difficile Ribotypes

Abstract: C. difficile infection is associated with disturbed gut microbiota and changes in relative frequencies and abundance of individual bacterial taxons have been described. In this study we have analysed bacterial, fungal and archaeal microbiota by denaturing high pressure liquid chromatography (DHPLC) and with machine learning methods in 208 faecal samples from healthy volunteers and in routine samples with requested C. difficile testing. The latter were further divided according to stool consistency, C. difficil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 42 publications
6
46
2
Order By: Relevance
“…Murine gut microbial structures that allow for C. difficile colonization are commonly associated with an increase in members from the Proteobacteria phylum (Enterobacteriaceae family) and a decrease in overall diversity (6,7,33). This is consistent with human studies in which high levels of Proteobacteria and low levels of Bacteroidetes in the gut microbiota were associated with C. difficile colonization (34)(35)(36)(37)(38)(39).…”
Section: Discussionsupporting
confidence: 80%
“…Murine gut microbial structures that allow for C. difficile colonization are commonly associated with an increase in members from the Proteobacteria phylum (Enterobacteriaceae family) and a decrease in overall diversity (6,7,33). This is consistent with human studies in which high levels of Proteobacteria and low levels of Bacteroidetes in the gut microbiota were associated with C. difficile colonization (34)(35)(36)(37)(38)(39).…”
Section: Discussionsupporting
confidence: 80%
“…[83][84][85][86][87] Only a handful of studies have detailed the structure of the human gut microbiota after C. difficile infection, and human samples prior to CDI are limited ( Table 2). [88][89][90][91][92][93] The most recent study comes from Antharam et al 2013 who compared the fecal microbiota of healthy subjects (n = 40) to those with antibiotic-associated diarrhea (AAD, n = 36) and C. difficile infection (CDI, n = 39). 88 Decreased microbial diversity and species richness was observed in the fecal microbiota of AAD and CDI cases compared with healthy controls.…”
Section: Animal Models and Human Studies Of C Difficile And/or Gut Mmentioning
confidence: 99%
“…In contrast, many of these bacteria are susceptible to fidaxomicin and vancomycin (21). Several studies found a greater abundance of members of the genus Bifidobacterium in the feces of individuals considered resistant to CDI infection than in the feces of those susceptible to recurrence (22,23). Many of these human microbiome studies of CDI and controls reveal substantial changes in the complex gut microflora but have yet to correlate these changes with specific antibiotic therapy.…”
mentioning
confidence: 99%